Correlation of Laser-Accelerated Electron Energy with Electromagnetic Pulse Emission from Thin Metallic Targets - Aurelian Marcu; Mihai Stafe; Andreea Groza; Mihai Serbanescu; Razvan Ungureanu; Gabriel Cojocaru; Constantin Diplasu; Bogdan Mihalcea; Mihai Ganciu; Constantin Negutu; Georgiana Giubega; Niculae Puscas (Applied Sciences)
High-power pulsed lasers are used more and more as tools for particle acceleration. Characterization of the accelerated particles in real-time and monitoring of the electromagnetic pulses (EMPs) during particle acceleration are critical challenges in laser acceleration experiments. Here, we used the CETAL-PW laser facility at NILPRP for particle acceleration from different thin metallic targets, at laser intensities of the order of <semantics>3×1021</semantics> W/cm2. We investigated the dependence of EMP amplitude (EMPA) and the accelerated electrons’ maximal energy (AEME), on thickness, resistivity, and atomic number of the target. We have found a quasi-linear dependence between EMPA and AEME and propose an analytical model for the GHz EMP emission. The model considers the neutralization current flowing through the target stalk as the main source of the EMP in the GHz domain, the current being produced by the positive charge accumulated on the target after the electron’s acceleration from the rear side of a metallic target. The data presented here support the possibility of using EMP signals to characterize the laser-accelerated particles in a real-time non-invasive way.